Introduction to nanofiber materials - Ko, Frank K., 1947-; Wan, Yuqin (Cambridge University Press, 2014)
"Presenting the latest coverage of the fundamentals and applications of nanofibrous materials and their structures for graduate students and researchers, this book bridges the communication gap between fiber technologists and materials scientists and engineers. Featuring intensive coverage of electroactive, bioactive and structural nanofibers, it provides a comprehensive collection of processing conditions for electrospinning and includes recent advances in nanoparticle/nanotube-based nanofibers. The book also covers mechanical properties of fibers and fibrous assemblies, as well as characterization methods"--Resumé vydavatele
Keywords: nanovlákna; vláknové kompozitní materiály; polymery; nanofibers; fibre reinforced composites; polymers; monografie; monographs